Modelling environmental equity: Exposure to environmental urban noise pollution in Birmingham, UK - Julii S. Brainard; Andrew P. Jones; Ian J. Bateman; Andrew A Lovett (University of East Anglia, The Centre for Social and Economic Research on the Global Environment (CSERGE), 2003)
This paper examines the extent to which inequalities in noise exposure are present in the city of Birmingham in the English midlands. Estimates of road and rail noise levels were made using established sound propagation models and were combined with data on noise generated from the city's airport. Demographic details from the 1991 UK Census provided information on population age, ethic makeup, and deprivation. No relationship was established between noise exposure and population age, and there was only rather weak evidence of an association between noise exposure and ethnicity. However, greater disparities were observed in estimated noise exposures and levels of socio-economic deprivation. The implications of these findings with regard to possible efforts to reduce urban noise levels are discussed.
Keywords: 330; Environmental Equity; Geographical Information Systems; Noise Pollution; Population Exposure; Lärm; Räumliche Verteilung; Umweltplanung; Birmingham; Großbritannien